THE FUNCTION OF SUFFIX -sA IN CHAGATAI TURKISH - Filiz Meltem ERDEM UÇAR (Fırat University, 2019)
The suffix -sA is called conditional or subjunctive as it is fundamentally used to link a state or action with a mood of condition or wish/purpose, respectively. The use of -sA as conditional clause is an ongoing function since the early periods of Turkish language. This suffix does not provide a state of condition when it is used i